Fractal-based multi-feature texture description - Kasparis, Takis; Tzannes, Nicolaos S.; Bassiouni, Mostafa A. (My University, 1991)
Fractal geometry receives recently increasing attention in analyzing natural scenes. The fractal dimension of a surface image has been used as segmentation feature, but since it is not sufficient to characterize important configurative texture characteristics, additional features are necessary. In this work we use a combination of fractal and non-fractal features to segment and classify natural textures.
Keywords: Fractals; Image processing; Computer vision